Safeguarding and promoting the well-being of children, families and communities - Scott, Jane, 1968-; Ward, Harriet, 1948-; Eagle, Maria (Child welfare outcomes, 2005)
Improving the well-being of children is more effective when social care professionals work with the children's parents, families, and communities. This collection brings together innovative interventions designed to nurture children's health and welfare, and analyses which types of programmes are most effective and why. The contributors explore the impact of poverty on children's development and assess national initiatives set up to assess and reduce need. They present examples from the UK, US, Canada, and Australia of specific interventions to counter or prevent difficulties in the domains of child development, parenting capacity and wider environmental factors. Many contributions demonstrate the importance of engaging with service users and helping communities to shape and direct their own programmes for change. The final section of the book presents useful approaches to assessing and evaluating services. Demonstrating the need for close inter-agency collaboration and "joined up" services, this book is essential reading for policy makers, managers and practitioners in child welfare agencies, and social work academics and students.